Morphofunctional characteristics of working mules in mountain areas of the Colombian Central Andes (Acta Scientiarum. Animal Sciences, 2019)
The application of morphofunctional measurements allows the selection of suitable animals to perform working activities and ensure that animal maximum capacities are not exceeded. Mules are commonly used by small farmers for agricultural work in mountain areas where the access is extremely difficult. We aimed to estimate the functionality indexes of working mules in mountain areas of the Colombian Central Andes. A total of 94 adult mules were evaluated for withers height, thoracic perimeter, body length, neck length, and body weight, which were used to determine the body index (BI), proportionality index (PI), and load carriage index (LCI). Descriptive statistics, analysis of correlations, and principal component analysis were performed. Males presented higher morphometric measurements than females. There was a negative correlation between BI with PI and LCI. The principal component analysis was able to merge characteristics in two components explaining 81.78% of the variance in the indexes. These results demonstrated that working mules in the studied area have morphometric characteristics that define them as mesolinear animals with a low frame and broad chest, and these characteristics can function as a guide to identify desirable conformation indices for working mules, determining values of adequate load, respecting animal welfare.